Evaluation Of Phytoconstituents And Antioxidant Properties Of Polyherbal Formulations As Potential Antidiabetic Agents - Singh, Yashwant; Sonker, Shilpi (Journal of Neonatal Surgery, 2025)
The aim of the study to investigate the phytochemical and antioxidant activity of polyherbal formulation in antidiabetic potential. Ethanolic extract of the polyherbal formulation was prepared by the Soxhlation process, Phytochemical screening, Total Phenolic Content and Total Flavonoid Content of the extracts were estimated using standard methods. Extracts were analysed for its antioxidant potential using DPPH, and Reducing power methods to assay their free scavenging activity. Results shows that plant extract (Tinospora Cordifolia and Epipremnum aureum) contains Flavonoids 0.65±0.03 and 55.2±0.05 mg/g, Total phenol 5.2±0.29mg/g and 8.3±0.19mg/g, preliminary phytochemical screening revealed the presence of tannins, alkaloids, flavonoids, glycosides. Antioxidant study for DPPH and reducing power of plant extract were 37.1±0.31, 47±0.28 and 88.99±0.22, 43.8±0.18, at 100µg/ml respectively. these findings may provide efficient, supportive data on the use of medicinal herbs for treatment of numerous health ailments associated with the accumulation of harmful free radicals and reactive oxygen species. It was concluded that flavonoids component were present in all solvent extracts of T. cordifolia and Epipremnum aureum. TFC was high in methanolic leaves extract of T. cordifolia and Epipremnum aureum. Furthermore, these results of plant sources were found to be highly significant. study has revealed that the ethanol extract of T cordifolia and Epipremnum aureum contains substantial amount of phenolics and thus, can be inferred that these phenolics are responsible for its marked antioxidant activity